2020
DOI: 10.1161/strokeaha.119.027602
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Additional Rehabilitation After Botulinum Toxin-A on Upper Limb Activity in Chronic Stroke

Abstract: Background and Purpose— The aim of this trial was to determine the effect of additional upper limb rehabilitation following botulinum toxin-A for upper limb activity in chronic stroke. Methods— We conducted a multicenter phase III randomized trial with concealed allocation, blinded measurement, and intention-to-treat analysis. One hundred forty stroke survivors who were scheduled to receive botulinum toxin-A in any muscle(s) that cross the wrist because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The BoNT-A+PT group showed an improvement for cervical as well as for headache parameters, according to the idea that migraine responds better to combined treatments [ 36 ]. Moreover, our study results further support the evidence found in previous researches that observed that the combined treatment BoNT-A+PT is more effective than a mono-therapy in pelvic pain [ 37 ], upper limb spasticity [ 38 ], and chronic facial synkinesis [ 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…The BoNT-A+PT group showed an improvement for cervical as well as for headache parameters, according to the idea that migraine responds better to combined treatments [ 36 ]. Moreover, our study results further support the evidence found in previous researches that observed that the combined treatment BoNT-A+PT is more effective than a mono-therapy in pelvic pain [ 37 ], upper limb spasticity [ 38 ], and chronic facial synkinesis [ 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…The program was designed to be patient driven; it was mostly carried out at home supported by phone calls, home visits and occasional attendance at the clinic. We then conducted a Phase III randomised trial to determine the clinical effect of additional upper limb rehabilitation following botulinum toxin-A [ 10 ]. The findings suggested that, in stroke survivors attending a spasticity clinic who were scheduled to receive botulinum toxin-A to a muscle crossing the wrist, an additional 3 months of evidence-based movement training was no more effective than botulinum toxin-A plus usual care in terms of goal attainment and upper limb activity.…”
Section: Backgroudmentioning
confidence: 99%
“…Previous reports have indicated that the combination of BoNT-A and splint therapy can lead to positive improvements in finger spasticity and ROM 7 , 8 ) . There are also several reports indicating that taping is more effective than splints 9 , 10 ) . We think this is because taping complements the fingers’ state as they change in form and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Extension using splints prevented the deterioration of skin hypersensitivity and led to improvements in ROM. We believe that gradually modifying the shape of the splint to allow proper extension according to the changes in the patient, makes this measure effective 9 , 10 ) . We suggest that sustained extension (after correcting the splint in accordance with the improvement in the distal muscles and finger joint contracture) is effective in cases such as this patient.…”
Section: Discussionmentioning
confidence: 99%